Identification of Potential Pharmacoperones Capable of Rescuing the Functionality of Misfolded Vasopressin 2 Receptor Involved in Nephrogenic Diabetes Insipidus. (September 2016) - Smith, Emery; Janovick, Jo Ann; Bannister, Thomas D.; Shumate, Justin; Scampavia, Louis; Conn, P. Michael; Spicer, Timothy P.
Pharmacoperones correct the folding of otherwise misfolded protein mutants, restoring function (i.e., providing "rescue") by correcting their trafficking. Currently, most pharmacoperones possess intrinsic antagonist activity because they were identified using methods initially aimed at discovering such functions. Here, we describe an ultra-high-throughput homogeneous cell-based assay with a cAMP detection system, a method specifically designed to identify pharmacoperones of the vasopressin type 2 receptor (V2R), a GPCR that, when mutated, is associated with nephrogenic diabetes insipidus. Previously developed methods to identify compounds capable of altering cellular trafficking of V2R were modified and used to screen a 645, 000 compound collection by measuring the ability of library compounds to rescue a mutant hV2R [L83Q], using a cell-based luminescent detection system. The campaign initially identified 3734 positive modulators of cAMP. The confirmation and counterscreen identified only 147 of the active compounds with an EC50 of ≤5 µM. Of these, 83 were reconfirmed as active through independently obtained pure samples and were also inactive in a relevant counterscreen. Active and tractable compounds within this set can be categorized into three predominant structural clusters, described here, in the first report detailing the results of a large-scale pharmacoperone high-throughput screening campaign.